AN APPROACH OF COLLECTIVE SOLIDARITY FUND FROM CONTRIBUTIONS TO FONAVI - Avelino Sánchez, Esteban Marino (2015)
By the law 29625 approved by referendum in late 2010, the return of contributions to FONAVI was approved. In early 2012, the Bar Association of Callao put an unconstitutional claim against it. The Constitutional Court on the judgment of File No. 0007-2012-PI / TC, October 2012, declared the unconstitutional claim unfounded and interprets Article 1 of the stated Act; the return of contributions to the fund individually and collectively, in the first case the contributions made by workers, in the second case the contributions made by their employers, the state and others, what is called “collective solidarity fund”. Therefore, the problem is how to separate the collective solidarity fund every month and every year from the total collective contributions to FONAVI obtained in each period. From November 1993 to August 1998 discriminating the amounts collected by the SUNAT, 2,129 million is obtained, in 59 months, resulting in a monthly average of over $ 36 million; the FONAVI contributions to employers would have exceeded the four billion dollars.